1998
DOI: 10.1080/13102818.1998.10818988
|View full text |Cite
|
Sign up to set email alerts
|

Further Evidence for Glutenin Modifications in Winter Wheat (Triticum AestivumL.) Induced by Somaclonal Variation

Abstract: The high molecular weight (HlvfW)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…It could be effectively used as a marker for discrimination not only of Pryaspa and Pryaspa 1 but also of Pryaspa 1 from the observed biotypes of Yantar. The reduction of protein content corresponding to subunit 7 encoded by Glu-B1 locus was not observed in the other varieties included in this study, but has been described in previous studies (4).…”
Section: Resultsmentioning
confidence: 62%
“…It could be effectively used as a marker for discrimination not only of Pryaspa and Pryaspa 1 but also of Pryaspa 1 from the observed biotypes of Yantar. The reduction of protein content corresponding to subunit 7 encoded by Glu-B1 locus was not observed in the other varieties included in this study, but has been described in previous studies (4).…”
Section: Resultsmentioning
confidence: 62%
“…Deletion of HMW-GSs results from gene silencing. The gene silencing of HMW-GSs could be caused by the deletion of small chromosomal fragments and the alteration of promoter regions ( Upelniek et al, 1995 ; Beshkova et al, 1998 ; Liu et al, 2016 ). Single base substitutions in the coding region sequences also cause gene silencing in the deletion of HMW-GSs in wheat, which usually results from premature termination codons ( Chen et al, 2019 , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tissue culture can be used to induce variation to wheat storage protein alleles [ 58 59 ]. In regenerated plants from the immature embryo cultures of the common wheat line CS, the variation for one protein band and protein bands controlled by the locus, mostly for gliadins, were observed with frequencies of 0.11% and 0.69%, respectively [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In regenerated plants from the immature embryo cultures of the common wheat line CS, the variation for one protein band and protein bands controlled by the locus, mostly for gliadins, were observed with frequencies of 0.11% and 0.69%, respectively [ 58 ]. In the regeneration offspring from in vitro culture of immature embryos of four winter varieties, one plant lacking 1Bx7 and 11By9 at the Glu-B1 locus was found, and alteration at this locus with decreased expression occurred in only one wheat genotype [ 59 ]. In this study, we reported a somatic variation mutant AS208 lacking genes encoding 1Bx20 and 1By20 that was identified from the tissue culture offspring of a commercial winter variety, LX987.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation